Integrons and antimicrobial resistance in bacteria: A systematic review - Shariati, Aref; Sabzehali, Fattaneh; Goudarzi, Mehdi; Azimi, Hadi (Archives of Advances in Biosciences, 2018)
Resistance to antimicrobial agents is on the rise and this phenomenon not only leads to an increase in economic burden but may also cause serious therapeutic problems. Nowadays, it is known that horizontal transfer of resistance genes is a major cause for spreading antibiotic resistance genes in microbes. The previous studies have manifested that integrons play a significant role in horizontal transfer of antibiotic resistance. Integrons are in fact natural cloning and expression systems which have the ability to spread multi drug resistance (MDR) in bacteria. They are normally motionless but can be transferred through mobile genetic elements, for example plasmids and transposons. Integrons carry divergent gene cassettes that are rearranged under antibiotic selective pressure. It is based on the sequence of the integrase gene that various classes of integrons are known. Class 1 integron is the most prevalent type among bacteria. This review highlights the need for continuous surveillance to understand the dissemination of integron and multidrug resistance among different bacteria.